2021
DOI: 10.1097/shk.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Enhances the Microvascular Reactivity Through RhoA-ROCK Pathway in Female Mice During Hemorrhagic Shock

Abstract: Vascular hypo-reactivity plays a critical role inducing organ injury during hemorrhagic shock. 17b-estradiol (E2) can induce vasodilation to increase blood flow in various vascular beds. This study observed whether E2 can restore vascular hypo-reactivity induced by hemorrhagic shock, and whether E2 effects are associated with RhoA-Rho kinase (ROCK)-myosin light chain kinase phosphatase (MLCP) pathway. The hemorrhagic shock model (40 AE 2 mm Hg for 1 h, resuscitation for 4 h) was established in ovary intact sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, the interaction of the RhoA-ROCK signaling pathway with H 2 S is unclear in rat cerebral arteries. As shown in Figure 1b, compared to the control group, CSE and 3-MST protein expression in rat cerebrovascular ECs was obviously reduced by the RhoA agonist U 46619 32 (100 nmol/ L), and CSE but not 3-MST protein expression was significantly increased by the RhoA inhibitor C3 transferase 33 (C3TF, 1.0 μg/mL). U 46619 remarkably reduced but C3TF increased basic or ACh-increased H 2 S content in rat cerebrovascular ECs compared with that in the control group or the ACh group (Figure 1d).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…However, the interaction of the RhoA-ROCK signaling pathway with H 2 S is unclear in rat cerebral arteries. As shown in Figure 1b, compared to the control group, CSE and 3-MST protein expression in rat cerebrovascular ECs was obviously reduced by the RhoA agonist U 46619 32 (100 nmol/ L), and CSE but not 3-MST protein expression was significantly increased by the RhoA inhibitor C3 transferase 33 (C3TF, 1.0 μg/mL). U 46619 remarkably reduced but C3TF increased basic or ACh-increased H 2 S content in rat cerebrovascular ECs compared with that in the control group or the ACh group (Figure 1d).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Recent studies showed that ethinyl estradiol sulfate, an estrogenic derivative, blunted hemorrhagic shock induced-multiple harmful outcomes in rat and swine, and showed a broad prospect of clinical application (30,31). Our previous studies have demonstrated that E2 prolonged the survival time and normalized CD4 + T lymphocyte function of rats after hemorrhagic shock (19) and attenuated hemorrhagic shock-induced vascular hyporeactivity in mice (25). In this study, we applied the small animal pulmonary function assay system and confirmed that E2 treatment improved the pulmonary function evidenced by these indices including RI, FRC, PEF, and IC of hemorrhagic shock rats.…”
Section: Discussionmentioning
confidence: 99%
“…After pulmonary function measurement, the intestinal loop blood flow was recorded in all rats as previously described (25). Briefly, the rat received an abdominal operation at room temperature to expose the intestinal loop of about 15 cm upward of the cecum, which is tiled in a circle.…”
Section: Intestinal Loop Blood Flowmentioning
confidence: 99%
“…It should be pointed out that vascular contractility following hemorrhagic shock was studied by various methods, such as pressor response to NE in vivo (Zhao et al, 2012 ; Li et al, 2014 ), a reduced percentage of vascular diameter after NE administration in vivo (Li et al, 2014 ), and isolated vascular contractile response to gradient concentrations of NE in vitro (Duan et al, 2020 ; Yue et al, 2021 ). While all these methods clarified that hemorrhagic shock induced vascular hyporeactivity in various ways.…”
Section: Discussionmentioning
confidence: 99%